Estetska komponenta indeksa potrebe za ortodontskom terapijom kod adolescenata u Srbiji - Ilić, Jana; Daković, Dragana; Lekić, Margareta; Lemić, Tatjana; Čutović, Tatjana (Vojnosanitetski pregled, 2021)
Background/Aim. The biggest motivating factor for undertaking orthodontic treatment is poor dental aesthetics as a consequence of occlusal abnormalities. The aim of this study was to determine the need for orthodontic treatment, based on the aesthetic components of the Index of Orthodontic Treatment Need (IOTN), to compare the degree of aesthetic component of IOTN and the subjective perception of individuals about their dental aesthetics, but also to compare their evaluation of the aesthetic component of IOTN in comparison with the evaluation of the therapist. Methods. The study was conducted on a sample of 316 students aged 15–19 years who did not have an orthodontic treatment prior to the survey. The research was carried out using the IOTN. The IOTN consists of dental and aesthetic components based on which the need for therapy was determined. The aesthetic component of the index was noted by the therapist (specialist of orthodontics) as well as the subject. Results. According to the grades of subjects, the need for orthodontic treatment was present in 0.38% of male subjects and 2% of female subjects. According to the evaluations of the therapists, the need for orthodontic treatment was present in 7.52% of male subjects and 8% of female subjects. Observing all subjects, the need for orthodontic treatment was present in 0.63% of subjects, and according to the therapist, the need for orthodontic treatment was present in 7.59% of subjects. The mentioned difference was statistically significant. Conclusion. Obtained results show that there is a significant difference in evaluation of dental aesthetics and the need for orthodontic treatment between the subjects and therapists. This can be a cause for concern because patients who are not aware of their orthodontic abnormality can limit the need for further treatment.